Issues of education and upbringing in the pages of "Wielkopolanin" (1848-1850) - Kabacińska-Łuczak, Katarzyna (Saeculum Christianum. Pismo Historyczne, 2024)
The aim of the article is to attempt and show the “enlightenment” of the peasants of Greater Poland in the middle of the nineteenth century in the magazines addressed to them, especially in relation to matters of education and upbringing. The subject of the research is the information on educational issues raised in one of the magazines for the people – “Wielkopolanin,” which was published in the years 1848-1850. Among the educational issues raised, the most important was the promotion of national identity both at school and at home. Further, it covered such topics as the influence of teachers on patriotic activity (their attitudes, values, importance in the local community), the role of village nursery schools, and support for orphans.